2001
DOI: 10.1093/ajcn/74.2.248
|View full text |Cite
|
Sign up to set email alerts
|

The National Center for Health Statistics reference and the growth of Indian adolescent boys

Abstract: The NCHS reference data seem inadequate for this sample. Consideration should be given to developing appropriate reference data based on healthy adolescent populations from different ethnic groups. Issues of maturation-related variation in assessing growth during adolescence should be given particular attention.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
42
3
2

Year Published

2003
2003
2013
2013

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(52 citation statements)
references
References 16 publications
2
42
3
2
Order By: Relevance
“…Compared with a median menarcheal age of 14.16 y in Beijing girls in 1962, using probit analysis again (Ye et al, 1981), with a mean menarcheal age of 13.1 y in 1995, Beijing girls appear to experience pubertal maturation earlier than 30 y ago. In contrast, using the WHO reference data, De Onis et al (2001) reported a 50.5% prevalence of thinness and a 11.2% prevalence of stunting in 818 Indian boys aged 7 -16 y (both figures being much higher than those from our current study of Chinese girls), and indicated that the reference data seemed inadequate for their study sample of Indian children. Our current study, however, shows a significant difference in growth, maturation and bone mineral parameters by setting the cut-off for low body weight at BMI of 18.…”
Section: Discussioncontrasting
confidence: 98%
See 1 more Smart Citation
“…Compared with a median menarcheal age of 14.16 y in Beijing girls in 1962, using probit analysis again (Ye et al, 1981), with a mean menarcheal age of 13.1 y in 1995, Beijing girls appear to experience pubertal maturation earlier than 30 y ago. In contrast, using the WHO reference data, De Onis et al (2001) reported a 50.5% prevalence of thinness and a 11.2% prevalence of stunting in 818 Indian boys aged 7 -16 y (both figures being much higher than those from our current study of Chinese girls), and indicated that the reference data seemed inadequate for their study sample of Indian children. Our current study, however, shows a significant difference in growth, maturation and bone mineral parameters by setting the cut-off for low body weight at BMI of 18.…”
Section: Discussioncontrasting
confidence: 98%
“…They defined under-nutrition as age-and gender-specific BMI less than the 5th percentile of American adolescents between 1971 and 1974, as recommended by WHO Expert Committee (1995). However, the WHO-recommended BMI cut-off might not be applicable to Asian children and adolescents, given differences in race and socio-economic conditions (Chang et al, 1994;Daniels et al, 1997;Luciano et al, 1997;Schaefer et al, 1998;De Onis et al, 2001). Furthermore, no evidence of impaired health was provided to support the selection of BMI 5th percentile as the cut-off between under-nutrition and acceptable nutrition in the report by Wang et al (1998).…”
Section: Introductionmentioning
confidence: 99%
“…The BMI is known to differ between different ethnic groups, especially in the lower ranges and has not been validated as an indicator of malnutrition (De Onis et al, 2001;Deurenberg et al, 2002). In this study, the correlation between skin fold thickness and BMI was weaker in male than in female subject, illustrating that at low values, the fatfree body mass is an important determinant of BMI.…”
Section: Nutritional Status After Malaria Control In Vietnam Lq Hung mentioning
confidence: 55%
“…A marginally nourished population is much different from an industrialised country's reference population. Using the US criteria generally overrates the rate of malnutrition in developing countries (De Onis et al, 2001). This may frustrate statistical analysis by crowding of data in the tail of the distribution curves as well as the mathematical conversion of cutoff points to define desirable body dimensions.…”
Section: Introductionmentioning
confidence: 99%
“…The age-specific prevalence of CED was estimated using the 5th percentile of the reference data developed by Must et al (1991a, b) on the basis of the first US National Health and Nutrition Examination Survey (NHANES I), and recommended for international use by a World Health Organization (WHO) Expert Committee Excess male chronic energy deficiency (WHO, 1995). These reference data are also referred to as 'National Center for Health Statistics' (NCHS) growth reference (de Onis et al, 2001), or 'WHO-NCHS' reference data (Wang et al, 2002) that we also referred to in this paper. Recently, NCHS in the Centers for Disease Control and Prevention (CDC), US Department of Health and Human Services, updated the growth charts known as CDC growth charts for use in the US (Kuczmarski et al, 2000).…”
Section: Methodsmentioning
confidence: 99%